Robert Penn Warren - American Writers 44 : University of Minnesota Pamphlets on American Writers - West, Paul (Book collections on Project MUSE., 1964)
Robert Penn Warren - American Writers 44 was first published in 1964. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.